Mutagenesis of the melon Prv gene by CRISPR/Cas9 breaks papaya ringspot virus resistance and generates an autoimmune allele with constitutive defense responses - Nizan, Shahar; Amitzur, Arie; Dahan-Meir, Tal; Benichou, Jennifer I C; Bar-Ziv, Amalia; Perl-Treves, Rafael (Journal of experimental botany, 2023)
Abstract The majority of plant disease resistance (R) genes encode nucleotide binding-leucine-rich repeat (NLR) proteins. In melon, two closely linked NLR genes, Fom-1 and Prv, were mapped and identified as candidate genes that control resistance to Fusarium oxysporum f.sp. melonis races 0 and 2, and to papaya ringspot virus (PRSV), respectively. In this study, we validated the function of Prv and showed that it is essential for providing resistance against PRSV infection. We generated CRISPR/Cas9 [clustered regularly interspaced palindromic repeats (CRISPR)/CRISPR-associated protein 9] mutants using Agrobacterium-mediated transformation of a PRSV-resistant melon genotype, and the T1 progeny proved susceptible to PRSV, showing strong disease symptoms and viral spread upon infection. Three alleles having 144, 154, and ~3 kb deletions, respectively, were obtained, all of which caused loss of resistance. Interestingly, one of the Prv mutant alleles, prvΔ154, encoding a truncated product, caused an extreme dwarf phenotype, accompanied by leaf lesions, high salicylic acid levels, and defense gene expression. The autoimmune phenotype observed at 25 °C proved to be temperature dependent, being suppressed at 32 °C. This is a first report on the successful application of CRISPR/Cas9 to confirm R gene function in melon. Such validation opens up new opportunities for molecular breeding of disease resistance in this important vegetable crop. Successful gene editing in melon proves that an Rgene candidate, Prv, controls resistance to papaya ringspot virus, while one of the mutated alleles causes dwarfism and autoimmunity.